2015
DOI: 10.1097/gme.0000000000000280
|View full text |Cite
|
Sign up to set email alerts
|

Soy Isoflavones for Reducing Bone Loss Study

Abstract: Objectives To assess the overall safety and potential endometrial stimulation of soy isoflavone tablets consumed (3-year) by postmenopausal women. To determine the endometrial thickness response-to-treatment among compliant women, taking into account hormone concentrations and other hypothesized modifying factors. Methods We randomized healthy postmenopausal women (45.8–65.0 years) to placebo control or two doses (80 or 120 mg/day) of soy isoflavones at two sites. We used intent-to-treat (N=224) and complian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Likewise, in a 3-year study, postmenopausal women given 80 or 120 mg of soya isoflavones daily showed no changes in thyroid function (32) . The authors of these recent publications have concluded that genistein and probably other isoflavones appear to show a good profile of safety in regard to thyroid function (33) .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in a 3-year study, postmenopausal women given 80 or 120 mg of soya isoflavones daily showed no changes in thyroid function (32) . The authors of these recent publications have concluded that genistein and probably other isoflavones appear to show a good profile of safety in regard to thyroid function (33) .…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies shown that given isoflavone product to postmenopausal women might relieve menopausal symptoms such as hot flushes and vaginal dryness [ 8 , 9 ]. There are also studies evaluated the effect of oral isoflavone supplementation on endometrial thickness, a risk factor of endometrial cancer [ 10 - 32 ]. However, the results were not consistent, and the sample sizes were relatively small (vary from 15 to 401).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review published in 2006 that included 14 clinical trials found that the totality of the evidence showed that neither soyfoods nor isoflavones adversely affect thyroid function in euthyroid men or women [402]. Studies published since this review [403,404,405,406,407], which include two that were three years in duration [408,409], are supportive of this conclusion as is the conclusion of the EFSA that isoflavone supplements do not affect thyroid function in postmenopausal women [108]. …”
Section: Thyroid Functionmentioning
confidence: 99%